Frequency Regulation of Stand-Alone Synchronous Generator via Induction Motor Speed Control Using a PSO-Fuzzy PID Controller - Masoud Elhawat; Hüseyin Altınkaya (Applied Sciences)
This paper introduces a novel approach to frequency regulation in stand-alone synchronous generators by combining particle swarm optimization (PSO) with a Fuzzy PID controller. This study compares three control methods: a programmable logic controller (PLC)-based PID, a Fuzzy PID, and a PSO-Fuzzy PID controller. An experimental setup is implemented using real physical equipment, including an asynchronous motor, a synchronous generator, and various power and control components. The system is monitored and controlled in real-time via an S7-1215 PLC with the TIA Portal V17 interface, and the controllers are designed using MATLAB/Simulink. PLC-MATLAB communication is implemented using the KEPServerEX interface and the OPC UA protocol. The PSO-Fuzzy PID controller demonstrates superior performance, reducing overshoot, undershoot, and settling time compared to the other methods. These results highlight the effectiveness and real-time applicability of the PSO-Fuzzy PID controller for industrial frequency control, especially under varying load conditions and the nonlinear characteristics of the synchronous generator.